Towards a context-flexible methodology for automated reviewer recommendation - Decoppet, Guillermo Omar (2025)
This essay proposes the adoption of a cultural socio-technical perspective for the development of an automated methodology for recommending reviewers in publications in the field of Science and Technology. The objective is to argue about the main guidelines to be considered so that such a methodology is flexible and dynamically adapts to the specific requirements of an Editorial Board (EB), in line with its policies and practices for selecting evaluators. Starting from a systematic and updated mapping of research on automatic recommendation of reviewers, and based on the theoretical framework of the Dynamic Intermedial Device, a study was carried out focusing on a scientific publication in Education Sciences from a research institute in Argentina. As part of the analysis, a survey was designed for members with experience in EB, which allowed obtaining key information. The results underline the importance of the EB establishing consensus to define the inclusion of various factors and their configuration parameters, which gives flexibility to the methodology. It is also highlighted that socio-technical participation is essential to ensure that an IT innovation responds adaptively to different contexts through the weighted inclusion of multiple factors, using advanced natural language processing techniques.